c-Abl tyrosine kinase down-regulation as target for memory improvement in Alzheimer’s disease - León, Rilda; Gutiérrez, Daniela A.; Pinto, Claudio; Morales, Cristian; de la Fuente, Catalina; Riquelme, Cristóbal; Cortés, Bastián I.; González-Martin, Adrián; Chamorro, David; Espinosa, Nelson; Fuentealba, Pablo; Cancino, Gonzalo I.; et al. (Frontiers in Aging Neuroscience, 2023)
Background Growing evidence suggests that the non-receptor tyrosine kinase, c-Abl, plays a significant role in the pathogenesis of Alzheimer’s disease (AD). Here, we analyzed the effect of c-Abl on the cognitive performance decline of APPSwe/PSEN1ΔE9 (APP/PS1) mouse model for AD. Methods We used the conditional genetic ablation of c-Abl in the brain (c-Abl-KO) and pharmacological treatment with neurotinib, a novel allosteric c-Abl inhibitor with high brain penetrance, imbued in rodent’s chow. Results We found that APP/PS1/c-Abl-KO mice and APP/PS1 neurotinib-fed mice had improved performance in hippocampus-dependent tasks. In the object location and Barnes-maze tests, they recognized the displaced object and learned the location of the escape hole faster than APP/PS1 mice. Also, APP/PS1 neurotinib-fed mice required fewer trials to reach the learning criterion in the memory flexibility test. Accordingly, c-Abl absence and inhibition caused fewer amyloid plaques, reduced astrogliosis, and preserved neurons in the hippocampus. Discussion Our results further validate c-Abl as a target for AD, and the neurotinib, a novel c-Abl inhibitor, as a suitable preclinical candidate for AD therapies.